2015
DOI: 10.1016/j.cortex.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selective attention and speech acoustics on neural speech-tracking in a multi-talker scene

Abstract: Attending to one speaker in multi-speaker situations is challenging. One neural mechanism proposed to underlie the ability to attend to a particular speaker is phase-locking of low-frequency activity in auditory cortex to speech’s temporal envelope (“speech-tracking”), which is more precise for attended speech. However, it is not known what brings about this attentional effect, and specifically if it reflects enhanced processing of the fine structure of attended speech. To investigate this question we compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
139
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 79 publications
16
139
1
Order By: Relevance
“…examined the neural responses to vocoder speech embedded in stationary broadband noise and found that delta band neural response enhanced with increasing spectral resolution and this enhancement correlated with speech comprehension scores. Rimmele et al (2015) further demonstrated that spectral resolution influences not only neural tracking of speech but also differentially influences the neural tracking of attended and unattended speech streams, in the case when the attended and unattended speech streams had different spectral resolutions. Different from these studies, we (1) systematically examined the effect of spectral degradation on selective attention in a competing background by varying the number of vocoder channels and (2) investigated the relationship between neural modulation responses and speech comprehension ability.…”
Section: Introductionmentioning
confidence: 90%
“…examined the neural responses to vocoder speech embedded in stationary broadband noise and found that delta band neural response enhanced with increasing spectral resolution and this enhancement correlated with speech comprehension scores. Rimmele et al (2015) further demonstrated that spectral resolution influences not only neural tracking of speech but also differentially influences the neural tracking of attended and unattended speech streams, in the case when the attended and unattended speech streams had different spectral resolutions. Different from these studies, we (1) systematically examined the effect of spectral degradation on selective attention in a competing background by varying the number of vocoder channels and (2) investigated the relationship between neural modulation responses and speech comprehension ability.…”
Section: Introductionmentioning
confidence: 90%
“…If the present LFO modulations cannot be explained by shifts in the parsing windows for speech segmentation, they may alternatively reflect an attentional modulation of acoustic processing, i.e., an enhanced neural excitability to particular acoustic features as has previously been reported for various kinds of sound stimuli (Besle et al 2011;Cravo et al 2013;Gomez-Ramirez et al 2011;Lakatos et al 2008;Rimmele et al 2015;Schroeder and Lakatos 2009a;Stefanics et al 2010;Zion-Golumbic et al 2013). One possibility is that the observed top-down effects reflect the processing of nonlexical speech information relevant for speech segmentation.…”
Section: Brain Oscillatory Mechanisms Of Linguistic Parsingmentioning
confidence: 99%
“…Delta oscillations were shown to delineate the perceived linguistic structure (phrases and sentences) within continuous speech, suggesting that LFO may be actively relevant for the parsing of smaller linguistic units such as words or syllables, which is the focus of this study. So far, the strength of LFO entrainment has been reported to systematically correlate with speech intelligibility (Ahissar et al 2001;Ding and Simon 2013;Doelling et al 2014;Gross et al 2013;Peelle et al 2013;Rimmele et al 2015), implying that LFO may be relevant for word segmentation. However, and importantly, speech intelligibility was also confounded with changes in the acoustic properties of the speech signal, leaving open the possibility that the observed modulations of LFO were driven by acoustic cues.…”
mentioning
confidence: 99%
See 2 more Smart Citations